Uso de bioestimulantes à base de substâncias húmicas e extrato de algas no desenvolvimento inicial do arroz de terras altas - Faria, Ohana Cristina Oliveira (2018)
The objective of the present work was to evaluate the effect of two biostimulants on the initial development of upland rice, one algae extract and the other humic substance. The experiment was located in a completely randomized experimental design (DIC), with three replications and seven treatments, being: 0.5; 1; and 2 times the dose recommended by the manufacturer of XT-95® (solid), and 0.5; 1 and 2 times the dose recommended by the manufacturer of K-Humate® (liquid), plus the control that received no application of the products, or dose 0. The following characteristics were evaluated: plant height, root length, dry matter of aerial part and roots, stomatal conductance and quantum efficiency of photosystem II. With the results obtained it is possible to affirm that the use of these products did not act directly on the evaluated variables